PENGARUH STRUKTUR MODAL TERHADAP RENTABILITAS EKONOMI PADA MEUBEL ROTAN IRMA JAYA DI KOTA PALU - Widyawati Widyawati (Universitas Tadulako, 2014)
The ability of a company to generate profit can be measured simply by looking at the successful and the ability of the company to productively utilize capital structure. This observation had several objectives i.e. to identify (1) the use of capital structure at Irma Jaya Rattan Furniture in Palu, (2) the development of economic rentability at Irma Jaya Rattan Furniture in Palu and (3) the influence of capital structure to economic rentability at Irma Jaya Rattan Furniture in Palu. Respondents were purposively taken in volving the employer and six employees of Irma Jaya Rattan Furniture. The relationship between capital structure and rentability was analyzed using a simple linear regression analysis, correlation coefficient analysis, coefficient determination analysis and hypothesis t test.During the last ten years, the use of capital structure at Irma Jaya Rattan Furniture has increased by three times of loan period. The company preferred to finance its business using its own funds rather than loans from other sources. The development of economic rentability at this company has increased its capital structure. The correlation coefficient (r) found was 0.71 indicating a positively strong relationship. The coefficient determination was 50.05% reflecting that the capital structure had a moderately well influence on the rentability rate while 49.5% was affected by external factors not included in the observation. The result of thet test showed thatt-calc was 2.858 which is greater than t-table(1.680). Thus, H0 is rejected but H1 is accepted suggesting that there is a significant correlation between the capital structure andthe economic rentability at Irma Jaya Rattan Furniture in Palu City. Key Words : Capital structure, economic rentability, and rattan furniture.